Exploring the Code Foundation: A Literature Review of Data Structures in C++ - Agung Yuliyanto Nugroho; Nur Hamid Sutanto (International Journal of Mechanical, Industrial and Control Systems Engineering, 2024)
This study aims to explore the foundation of code in the C++ programming language with a focus on data structures. Data structures are a fundamental component in efficient and effective software development. This literature review explores various types of data structures implemented in C++, including arrays, linked lists, stacks, queues, hash tables, and trees. An analysis is conducted on the basic principles and implementation of these data structures in the context of C++, taking into account the strengths and weaknesses of each structure. In addition, this study also discusses the evolution and comparison of data structure implementations from the perspective of performance and algorithm complexity. The results of this study provide in-depth insights into how data structures can affect the design and efficiency of C++ applications, as well as provide guidance for software developers in choosing the most appropriate data structures for their specific needs. The conclusions of this study highlight the importance of a deep understanding of data structures in software development and their contribution to the success of software projects.